2018
DOI: 10.1073/pnas.1809060115
|View full text |Cite
|
Sign up to set email alerts
|

Volatile loss following cooling and accretion of the Moon revealed by chromium isotopes

Abstract: SignificanceWith the exception of volatile elements, which are strongly depleted and isotopically fractionated, the Moon has chemical and isotopic signatures that are indistinguishable from Earth’s mantle. Reconciliation of these properties with Moon formation in a high-energy giant impact invokes evaporative loss of volatile elements, but at conditions that are poorly known. Chromium isotopic fractionation is sensitive to temperature variations and liquid–gas equilibration during evaporation. We measure an is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 66 publications
3
74
0
Order By: Relevance
“…Recently, studies have found that partial melting of the mantle may cause a small but detectable (~ 0.4‰ of δ 53/52 Cr NIST SRM 979 ) stable Cr isotopic fractionation (Schoenberg et al , Xia et al ). The oxygen fugacity variation may dominate the mass‐dependent chromium stable isotope fractionation in high‐temperature processes (Bonnand and Halliday , Shen et al , Sossi et al ). Thus, stable Cr isotopic fractionation may be observed between mantle and basalts, given the different Cr(II)/Cr(III) ratios of mantle melts and basaltic melts (Schoenberg et al ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies have found that partial melting of the mantle may cause a small but detectable (~ 0.4‰ of δ 53/52 Cr NIST SRM 979 ) stable Cr isotopic fractionation (Schoenberg et al , Xia et al ). The oxygen fugacity variation may dominate the mass‐dependent chromium stable isotope fractionation in high‐temperature processes (Bonnand and Halliday , Shen et al , Sossi et al ). Thus, stable Cr isotopic fractionation may be observed between mantle and basalts, given the different Cr(II)/Cr(III) ratios of mantle melts and basaltic melts (Schoenberg et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Xia et al () suggested that the δ 53/52 Cr NIST SRM 979 values of fresh fertile peridotites are −0.14 ± 0.12‰ on average and the variation of δ 53/52 Cr NIST SRM 979 values of mantle peridotites is caused by partial melting. The δ 53/52 Cr NIST SRM 979 value of BSE was given as −0.11 ± 0.11‰ by analysing komatiites (Sossi et al ). For the planetary processes, Moynier et al () suggested that there could be Cr isotopic fractionation during core segregation, as the δ 53/52 Cr NIST SRM 979 values of meteorites (− 0.2‰ to ∼ − 0.4‰) are lighter than that of the BSE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies did not find any Cr isotope difference between chondrites and BSE. 20,21 The very recent study of Sossi et al 22 In contrast, the double-spike technique has several advantages over the SSB method 17,[27][28][29] : (1) it can monitor and correct for the short-term drift in mass fractionation in the mass spectrometer; (2) it can minimize the effects of the difference in matrix composition between the sample and the standard; and (3) by adding the double spike before the sample preparation, mass fractionation caused by the purifying procedure can also be corrected even when the recovery of Cr is not 100%. Because mass-dependent isotopic fractionation occurs during mass spectrometry measurements, the "true" isotopic composition of the double spike cannot be measured directly.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies did not find any Cr isotope difference between chondrites and BSE . The very recent study of Sossi et al confirms Cr isotope fractionation between the Earth and the Moon, and attributes it to the Cr partitioning into an oxygen‐rich vapor phase in equilibrium with the proto‐moon.…”
Section: Introductionmentioning
confidence: 99%